2015
DOI: 10.1158/2159-8290.cd-14-1329
|View full text |Cite
|
Sign up to set email alerts
|

INPP4B Is a PtdIns(3,4,5)P3 Phosphatase That Can Act as a Tumor Suppressor

Abstract: Inositol polyphosphate 4-phosphatase B (INPP4B) has been identified as a tumor suppressor mutated in human breast, ovary, and prostate cancers. The molecular mechanism underlying INPP4B's tumor-suppressive role is currently unknown. Here, we demonstrate that INPP4B restrains tumor development by dephosphorylating the PtdIns(3,4,5)P3 that accumulates in situations of PTEN deficiency. In vitro, INPP4B directly dephosphorylates PtdIns(3,4,5)P3. In vivo, neither inactivation of Inpp4b (Inpp4bΔ/Δ) nor heterozygous … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
82
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 25 publications
4
82
0
Order By: Relevance
“…Similar to breast cancer, the observed loss of INPP4B expression in some prostate cancer patients was associated with a decreased time to relapse, while in vitro INPP4B depletion produced increased proliferation and Akt activation [5]. Among several other tissues, INPP4B has been recently been demonstrated to act as a bona fide tumor suppressor gene in human and mouse thyroid tissue [6,7]. Although several mechanisms by which INPP4B functions in the cell have been described, the predominant mechanism remains its ability to decrease cellular levels of PI(3,4)P 2 , and thereby inhibit Akt activation.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Similar to breast cancer, the observed loss of INPP4B expression in some prostate cancer patients was associated with a decreased time to relapse, while in vitro INPP4B depletion produced increased proliferation and Akt activation [5]. Among several other tissues, INPP4B has been recently been demonstrated to act as a bona fide tumor suppressor gene in human and mouse thyroid tissue [6,7]. Although several mechanisms by which INPP4B functions in the cell have been described, the predominant mechanism remains its ability to decrease cellular levels of PI(3,4)P 2 , and thereby inhibit Akt activation.…”
mentioning
confidence: 87%
“…Thyroid Cancer[6,7] Knockout of INPP4B can promote follicular-like thyroid cancer progression and metastasis in the context of PTEN haploinsufficiency AKT AKT Breast cancer [2,3,4] INPP4B-loss phenotype consistent with tumor suppressor funcƟon; expression restricted to ER-posiƟve mammary epithelial cells; loss of INPP4B protein is a marker of aggressive basal-like breast carcinomas TRENDS in Molecular Medicine…”
mentioning
confidence: 99%
“…For Vps34, the above myocardial tissue arrays and autopsy specimens were immunostained with anti-Vps34 Ab (clone EPR5301). Staining intensity of each cell was arbitrarily scored as being at level 0, +1, or +2 (41). This Vps34 protein level was multiplied by the percentage of immunoreactive cells among total cells counted to generate 3 groups: group 1, Vps34 protein expression score of less than 50 (low Vps34 protein); group 2, score 50-150 (medium); and group 3, score greater than 150 (high).…”
Section: Methodsmentioning
confidence: 99%
“…INPP4B, which dephosphorylates PtdIns(3,4)P 2 to generate PtdIns(3)P, is also frequently inactivated in basal-like breast cancer (Fedele et al, 2010;Gewinner et al, 2009). Loss of INPP4B leads to activation of AKT, and two studies by the Pandolfi and Sasaki laboratories showed that, in the context of PTEN inactivation, INPP4B is indeed a tumor suppressor and functions exclusively through AKT2 (Kofuji et al, 2015;Li Chew et al, 2015) ( Figure 1C). This is also consistent with a previous study that also showed that AKT2 is exclusively required for tumor maintenance in the setting of PTEN deficiency (Chin et al, 2014).…”
mentioning
confidence: 98%
“…through AKT1 and INPP4B/PTEN functioning through AKT2. Precisely how this specificity is achieved remains to be determined, although compartmentalization of both the lipid phosphatase and AKT isoform is likely to play a major role (Kofuji et al, 2015). It is also possible that AKT2 is preferentially activated by local pools of PtdIns(3,4)P 2 , such that, when PIPP is absent, less PtdIns(3,4)P 2 is generated and AKT1 becomes the dominantly active isoform ( Figure 1B).…”
mentioning
confidence: 99%